Buying and Selling Boycott Products and Maslahah Mursalah An Analysis of MUI Fatwa No. 83 of 2023 - Rufaida, Erty Rospyana; Alamsyah, Alamsyah (Jurnal Hukum Ekonomi Syariah, 2025)
The issuance of Fatwa No. 83 of 2023 by the Indonesian Ulema Council (MUI), which calls on Muslims to avoid products affiliated with Israel, has triggered a wide social, economic and religious discourse in Indonesia. The fatwa is not merely a moral call, but rather a normative directive in Islamic law rooted in the principle of maslahah mursalah - a consideration of the public good that is not explicitly mentioned in sacred texts, but is in line with the objectives of sharia. This study analyzes the fatwa through the perspective of contemporary Islamic fiqh and assesses its broader socio-economic implications. The research uses a descriptive qualitative method with a normative-theological approach, relying on literature study as the main technique of data collection, and supported by content analysis and critical review. The results show that this fatwa is based on strong theological foundations and strengthens the collective solidarity of Muslims towards the Palestinian cause. It introduces a model of non-violent resistance through economic jihad, encouraging Muslim consumers to practice ethical consumption. However, its implementation faces challenges, including limited access to information regarding product affiliations, consumer dependence on global brands, and economic risks for small businesses. This fatwa reflects a dynamic form of contemporary ijtihad, demonstrating the active engagement of scholars in responding to global injustices. Although not legally binding, these fatwas have strong normative authority in shaping Muslim consciousness towards justice, humanity and public good. This study emphasizes the importance of policy synchronization and public education to increase the practical impact of this fatwa in Indonesia's pluralistic society.